Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

La santé en contexte francophone minoritaire au Canada : 20 ans de recherche: Introduction - Bouchard, Louise; Savard, Jacinthe; Dumond, Morgan (Minorités linguistiques et société, 2024)

La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

English-language Health and Social Services Access in Québec. Comparison 2019-2023 - CROP (Community Health & Social Services Network, 2023)

L’accès en anglais aux services de santé et aux services sociaux au Québec. Version française du rapport comparatif 2023-2019 - CROP (Community Health & Social Services Network, 2024)

Accès aux services en santé dans la langue officielle de leur choix par les minorités francophones hors Québec. Analyse de données secondaires - Diaz Pinsent Mercier Research Inc (Consortium national de formation en santé, 2021)

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

L’usage de technologies de santé pour accéder à des soins virtuels : une enquête exploratoire pour mieux comprendre les besoins et attentes des francophones de l’Ontario - Grosjean, Sylvie; Giguère, Lauriane; Lessard, Lysanne; Dionne, Émilie (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons les résultats d’une étude visant à répondre à la question suivante : quels usages des technologies numériques de santé sont jugés accessibles et acceptables par les francophones de l’Ontario? Les résultats de cette enquête exploratoire montrent que l’accessibilité et l’acceptabilité des technologies de santé pour soutenir l’offre de soins virtuels chez les francophones de l’Ontario dépendent de plusieurs facteurs liés : a) à leur utilité perçue, b) à leur valeur sociale et leur intégration dans des usages existants, et c) à l’offre des technologies accessibles en français – de leur conception au support offert pour en accompagner les usages. Les résultats de l’étude nous invitent à considérer les questions à la fois communicationnelles (concordance linguistique patient/technologie), organisationnelles (intégration dans des pratiques et structures existantes) et éthiques qu’implique l’usage des technologies de santé visant à soutenir l’offre de soins virtuels pour les francophones de l’Ontario. Mots-clés : soins virtuels, technologies numériques de santé, acceptabilité, francophones, Ontario

Welfare services from a minority perspective. Explaining satisfaction with language-based welfare services among Swedish-speaking Finns - Himmelroos, Staffan; Vento, Isak; von Schoultz, Åsa (Linguistic Minorities and Society, 2021)

Bilingualism in the health system: The Catalan case - Ibáñez Ferreté, Òscar-Adrià; Mestres i Farré, Neus (Linguistic Minorities and Society, 2021)
Catalan-speaking citizens living in Catalonia have full, formal rights to use their language with all of their region’s administrations. Nevertheless, the available information on the knowledge and use of Catalan by civil servants shows that health care is a weak spot for regional administrations, due to the difficulty in covering all medical specialties. Plataforma per la Llengua has undertaken research in the form of a survey with a sample of 1,600 Catalan inhabitants, to ascertain the level of satisfaction with the enforcement of linguistic rights in public health and determine the scope of a potential language promotion policy that would have health care staff initiate conversations in Catalan. Results of government surveys suggest that language use (by both patients and providers) in the health care system, compared with language use in other areas of public administration, demonstrates the limits of the current regional language promotion policies in Catalonia. Keywords: catalan, linguistic minorities, linguistic rights, health and social services, language competencies

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Tensions linguistiques au Nouveau-Brunswick : attitudes à l’égard du bilinguisme dans le système de santé. - Landry, Michelle; Legault-Leclair, Jacob; McLaughlin, Gilbert (Minorités linguistiques et société, 2024)
Dans cet article, nous examinons les opinions des anglophones à l’égard du bilinguisme dans le système de santé. Les données proviennent d’un sondage mené par la firme Léger du 16 au 24 février 2021. Nous avons mesuré l’effet d’une série de variables sociodémographiques, de l’orientation politique et de l’accord avec un énoncé selon lequel les francophones constitueraient un groupe privilégié sur le fait d’être d’avis que les services bilingues sont suffisamment développés dans le secteur de la santé. En conclusion, les résultats indiquent que les électeurs des partis politiques conservateurs et du People’s Alliance ont en majorité tendance à estimer que le bilinguisme en santé est suffisamment développé. Les variables sociodémographiques et le fait d’affirmer que les francophones représentent un groupe privilégié ne sont pas des variables discriminantes dans notre analyse. Mots-clés : Bilinguisme, Nouveau-Brunswick, système de santé, Acadie, services en français

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

Le Réseau à l’écoute. Rapport à la communauté 2022-2023. - Réseau des services de santé en français de l’Est de l’Ontario (2024)
Le Réseau des services de santé en français de l’Est de l’Ontario (RSSFE ou Le Réseau) a lancé la nouvelle initiative Le Réseau à l’écoute en février 2022 auprès des membres du Réseau et de la communauté francophone de l’Est et du Sud-Est de l’Ontario. Il s’agit d’un espace privilégié pour entendre les expériences, tant positives que négatives, qu’ont les membres de la communauté francophone avec le système de santé. Ce premier rapport à la communauté sur Le Réseau à l’écoute couvre une période de 14 mois, portent sur 26 témoignages (représentent 51 expériences distinctes) reçus entre les mois de février 2022 et la fin de mars 2023.

Le Réseau à l’écoute. Rapport à la communauté 2023-2024. - Réseau des services de santé en français de l’Est de l’Ontario (2024)
Le Réseau des services de santé en français de l’Est de l’Ontario (RSSFE ou Le Réseau) a lancé l'initiative Le Réseau à l’écoute en février 2022 auprès des membres du Réseau et de la communauté francophone de l’Est et du Sud-Est de l’Ontario. Il s’agit d’un espace privilégié pour entendre les expériences, tant positives que négatives, qu’ont les membres de la communauté francophone avec le système de santé. Ce 2e rapport fait état de la collecte des données de l’année 2023-2024, au cours de laquelle Réseau à l'écoute a reçu 35 témoignages qui représentent 57 expériences uniques. En deux ans, Le Réseau à l’écoute a reçu 61 témoignages qui représentent 108 expériences uniques, dont une croissance de 35% du nombre de répondants dans la dernière année. Les expériences obtenues grâce au Réseau à l’écoute mettent en valeur la réalité de l’accès aux services de santé en français de même que les défis auxquels sont confrontés la communauté francophone lorsqu’il s’agit de recevoir des services de santé dans sa langueé

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Final Report – Improving the Francophone Experience in Healthcare - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

Rapport final – Amélioration de l’expérience des francophones dans les soins de santé - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange Van; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.

L’expérience des francophones des soins et des services en contexte linguistique minoritaire : bilan et perspectives. - Sauvé-Schenk, Katrine; Savard, Jacinthe; Miljours, Jean-Christophe; Bouchard, Louise (Minorités linguistiques et société, 2024)
L’objectif de cet article est de présenter un état des lieux de la recherche qui porte sur l’expérience des bénéficiaires de services sociaux et de santé en contexte francophone minoritaire. On y traite des perceptions envers les services sociaux et de santé, de la demande de services en français ainsi que des expériences d’accès à des services en français, des barrières linguistiques et de la navigation dans le système de santé. On y traite aussi les perspectives qu’apportent les recherches en cours pour 1) mieux saisir les perceptions des francophones à l’égard de l’utilisation des technologies en santé afin d’améliorer leur accès aux services en français et 2) intégrer la mesure de la perception des usagers à l’évaluation continue des services en français. Mots-clés : expérience patient, minorité linguistique, francophone, système de santé, Canada

Vers de nouvelles approches en santé mentale : possibilités et limites pour les francophones en situation minoritaire à Terre-Neuve-et-Labrador et aux Territoires du Nord-Ouest - Savard, Sébastien; van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Oukouami D, Ghisleine; Michel, Jean Nephetaly (Canadian Social Work Review / Revue canadienne de service social, 2024)
De nouvelles approches axées sur la cybersanté mentale l’aide à la navigation du système, les cliniques sans rendez-vous, ainsi que les approches plus traditionnelles comme les lignes d’aide et de crise cohabitent afin de promouvoir ou d’intervenir précocement en santé mentale. Comment ces interventions répondent-elles aux besoins des francophones en contexte linguistique minoritaire alors que la communication est au coeur d’une consultation réussie? Objectif : Documenter six initiatives à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest. Méthode : Études de cas, incluant trente-six entrevues semi-dirigées auprès des autorités sanitaires, des fournisseurs de soins et des usagers. Résultats : La gratuité, l’anonymat, la rapidité, la présence des pairs travailleurs, l’absence de jugement et des démarches simples facilitent l’accès aux programmes. Parmi les limites, l’insuffisance de services en français et l’accent sur les thérapies brèves peuvent affecter la continuité des services, notamment pour les usagers francophones. Conclusion : Malgré les efforts pour améliorer l’offre de services en santé mentale aux francophones, des lacunes subsistent. L’article présente certaines stratégies qui permettraient d’améliorer l’offre de ces services. Mots-clés : Santé mentale, cybersanté mentale, initiatives novatrices, Terre-Neuve-et-Labrador, Territoires du Nord-Ouest, soins par paliers, francophones en situation minoritaire

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Pratiques novatrices en santé mentale pour les populations de langue officielle minoritaire à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Savard, Sébastien; Oukouomi, G.; Michel, J. N. (Université d'Ottawa, Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Les expériences de patients francophones qui se présentent fréquemment à l'urgence pour des raison de santé mentale - Vandyk, Amanda; Lightfoot, Sophie; Levesque, Kristine; Domecq, Marie-Cécile.; Jacob, Jean Daniel (Recherche en soins infirmiers, 2022)
Introduction: Language and communication are pivotal to the safe care and management of people with mental health disorders, particularly when these patients are linguistic minorities. Objectives/method: To explore these experiences within linguistic minority populations by completing a literature review and qualitative interviews. Interviews were conducted in Ottawa, Canada, with francophone patients. The studies included in the review represented the international literature on linguistic minorities in general. Results: Overall, the experiences described in the published articles were similar to the participants' own experiences, suggesting that barriers to care exist even in settings mandated to provide services in both official languages. Discussion/conclusion: There are many barriers to the provision of mental health care services, regardless of the dominant language. However, we identified an internalized sense of responsibility felt by linguistic minority patients, who feel compelled to compensate for or fill in the language gaps of providers. Keywords: health services accessibility; language; mental health; qualitative research; rapid review.